Reinforcing Patient Acquisition through Integrated Community Healthcare: Qualitative Analysis - Jessica Hermawan; Hilda Yunita Wono (Journal La Medihealtico, 2026)
Healthcare institutions in semi-rural areas face increasing challenges in attracting general patients due to competition and shifting service expectations. Mojowarno Christian Hospital addresses this issue through its Executive Clinic, a premium service unit aimed at improving patient experience and service reach. This study employs a quasi-qualitative case study with a post-positivist lens to analyze the hospital’s marketing management strategy across the seven elements of the service marketing mix. Data were obtained from in-depth interviews and internal documents and analyzed using NVivo-assisted thematic coding. The findings identify three strategic pillars: enhancing service value through premium and personalized care, expanding accessibility via integrated community outreach and multi-channel service pathways, and strengthening visibility through digital communication, referrals, and community engagement. These findings produce an Integrated Community Healthcare Strategy relevant for semi-rural Christian-based hospitals. The study is limited to one site; future research may test the model quantitatively or compare across hospital types.